Public Space for Disabled Students in Higher Education - Puspitasari, Maria (Institut Komunikasi dan Bisnis LSPR, 2024)
Students with disabilities have been treated discriminative practices in their space of movement in society, including on campus. The facilities available on campus do not yet reflect the concept of public space as a manifestation of democracy. The purpose of this study was to identify the experiences and meanings of disabled students related to the public spaces available on campus. The study used a qualitative approach, and utilized interviews with five research subjects, four of whom were disabled students, and one of Commissioner with disabilities. Observation was the method for triangulation. The study showed that public spaces were designed without considering aspects of accessibility, comfort, and safety for disabled students. This resulted in a strong awareness that they were marginalized and ignored in the public space policy process. The study also showed the importance of take notice to a several elements in the process of building a fair and equal public space, by prioritizing the principle of participation that show interest to aspects of social inclusion and no party is ignored in the process. For this reason, collaborative cooperation is needed between the campus by encouraging the government to form regulations to develop public spaces. The stakeholders involved first are people with disabilities, in collaboration with campus stakeholders and other civil society organizations.